Specialist integrated haematological malignancy diagnostic services: an Activity Based Cost (ABC) analysis of a networked laboratory service model. Issue 4 (28th January 2015) - Dalley, C; Basarir, H; Wright, J G; Fernando, M; Pearson, D; Ward, S E; Thokula, P; Krishnankutty, A; Wilson, G; Dalton, A; Talley, P; Barnett, D; et al.
Abstract : Aims: Specialist Integrated Haematological Malignancy Diagnostic Services (SIHMDS) were introduced as a standard of care within the UK National Health Service to reduce diagnostic error and improve clinical outcomes. Two broad models of service delivery have become established: 'co-located' services operating from a single-site and 'networked' services, with geographically separated laboratories linked by common management and information systems. Detailed systematic cost analysis has never been published on any established SIHMDS model. Methods: We used Activity Based Costing (ABC) to construct a cost model for our regional 'networked' SIHMDS covering a two-million population based on activity in 2011. Results: Overall estimated annual running costs were £1 056 260 per annum (£733 400 excluding consultant costs), with individual running costs for diagnosis, staging, disease monitoring and end of treatment assessment components of £723 138, £55 302, £184 152 and £94 134 per annum, respectively. The cost distribution by department was 28.5% for haematology, 29.5% for histopathology and 42% for genetics laboratories. Costs of the diagnostic pathways varied considerably; pathways for myelodysplastic syndromes and lymphoma were the most expensive and the pathways for essential thrombocythaemia and polycythaemia vera being the least. Conclusions: ABC analysis enables estimation of running costs of a SIHMDS model comprised of 'networked' laboratories. Similar cost analyses for other SIHMDS models covering varying populations are warranted to optimise quality and cost-effectiveness in delivery of modern haemato-oncology diagnostic services in the UK as well as internationally.